Subthreshold Kink Effect in Gate-All-Around MOSFETs Based on Void Embedded Silicon on Insulator Technology - Yuxin Liu; Qiang Liu; Jin Chen; Zhiqiang Mu; Xing Wei; Wenjie Yu (IEEE Journal of the Electron Devices Society)
The kink effect of gate-all-around (GAA) MOSFET has been experimentally validated by our GAA devices fabricated on a void embedded silicon-on-insulator (VESOI) substrate. In this VESOI GAA device, a consistent and favorable decrease in subthreshold swing (SS) is observed as $V_{ d}$ increases, which has rarely been reported in devices with other gate structures. In particular, the SS of the device reaches the minimum ~0.1mV/dec with no discernable hysteresis window at $V_{ d} {=} 4.5$ V under ambient condition. Further device simulation strongly confirms the unique role of the GAA controllability over the hysteresis-free kink process. These findings contribute to a better understanding of kink behaviors within GAA device for potential application.